A constituição do sujeito-leitor em projetos de leitura : ressignificações a partir de instâncias ideológicas - Santos, Claudiana dos (2018)
The studies about reading in Brazil are developed under different perspectives, so this research aims to understand the production of meanings about the constitution of the reader and the social memory of reading from textual / discursive materialities that point to the the functioning of discursive formations and, consequently, interdiscourse.In order to achieve this goal, we selected reading projects, reports and documents that circulate in ideological instances of economic, juridic, religious and educational space. With the theoretical-methodological background of French Line Discourse Analysis we conducted the discursive study of the subject-reader object. The theoretical framework is subsidized by Michel Pêcheux (1995;1997; 2015), Eni P. Orlandi (2003;2007; 2008; 2015), Maria do Rosário V. Gregolin (2006), S. Possenti (2003), José H. Nunes (1992;2003), Helena H. Brandão (2012) and Eduardo Guimarães (1996, 2013). The course of this analysis is constructed under the following categories: discourse, subject-form, ideology, interdiscourse, discursive formation, production conditions, corpus, file and clipping. Regarding the approach, the research presents a qualitative bias and for the composition of the empirical corpus we adopted documentary research. Taking into consideration the outcome of this study, the method identified that the economic instance takes back the sense of the mode of functioning of the subject of capitalism, since there are prizes and financial recognitions for the work of reading. In the juridical instance, the subjectreader is constituted from a model that recalls the memory of punishment, the knowledge that comes from submission to rules. In the religious instance, there is the erasure of the construction of the reading path and a work of disciplinarization of the subject-reader. In the educational instance, specifically in the objectives of PNLL, we identify the meanings of an "official discourse" that guarantees the liberalism of reading, aiming at the formation of a reading society. In all instances there is the functioning of discursive formations that take up the pedagogical practice. The senses operate in the dissemination of a culture that values and encourages reading, forcing the erasure of a historical memory in which the Brazilian "does not like to read." Thus, the constitution of the reader-subject occurs in the dispersion of the different types of reading.